Landslide susceptibility assessment on a large scale in the Podsljeme area, City of Zagreb (Croatia) - Sanja Bernat Gazibara; Marko Sinčić; Martin Krkač; Hrvoje Lukačić; Snježana Mihalić Arbanas (Journal of Maps, 2023)
ABSTRACTThe study presents a landslide susceptibility assessment on a large scale in the City of Zagreb (Croatia). The susceptibility analysis was performed using the Weight of Evidence model in the pilot area (21 km2) and applying the obtained weight values for each class of conditioning factors in the study area (130 km2). The input data were LiDAR-based landslide inventory and six conditioning factors derived from 5 m LiDAR DTM, 5 m SfM DEM, and geological and land-use maps. The validation of the susceptibility assessment for the study area was evaluated with a ROC curve, which showed a high prediction rate (AUC = 84.4%), similar to the prediction rate for the pilot area (AUC = 86.9%). Based on the results, it can be concluded that the proposed method for large-scale landslide susceptibility assessment, where susceptibility conditions are defined in smaller pilot areas, can be applied to larger research areas with similar geomorphological and geological conditions.